Agripreneurship Characteristics in Green Agribusiness - กำแพงเพชร, มรกต; ธรรมอภิพล, สวรรยา; สังข์รักษา, นรินทร์ (Business Administration and Management Journal Review, 2019)
As concern for the environment becomes a universal phenomenon, surely the profile of the ecologically conscious consumer has evolved along with this fundamental shift in public attitude. After the Green Economy, the role of the farmers worldwide has been developed to become an agricultural entrepreneur. The role aims at reducing the economic inequality and raising the social environment-friendly which are the goal of sustainable development (SDGS). The concept of Entrepreneurial Orientation is a new paradigm for driving the world economy. The development of a farmer is one of the Thailand 4.0 model goals. It is driving to reform the economic structure by changing a traditional agriculture to a modern agriculture. The farmers should have the Agripreneurship characteristics to become a successful farmer. The Agripreneurship characteristics will increase the ability to create and develop a profitable business in the changing business environment and increase the awareness of a new business opportunity. Furthermore, it will help farmers to build the business network and develop the skills of management, marketing and sale, and strategy management. Agripreneurship characteristics will help the agricultural entrepreneurs to be successful in Green Agribusiness.